An analysis of teachers’ questioning strategies during the classroom interaction in English for specific purposes - Sulistio, Yuliardi; Dwinata, Erna (Regalia Institute, 2023)
This research aimed to find out the questioning strategy used by lecturer in teaching English during the classroom interaction especially in online learning process. The method used in this research was descriptive qualitative. The participant in this study was an English lecturer at UBHI PGRI Tulungagung who teaches the English for Specific Purposes course. The researcher used purposive sampling by taking one lecturer as a participant. To gather the data, the writer used observation and interview. Based on the data analysis, it was found that the lecturer used several questioning strategies, based on four questioning strategies categories suggested by Wangru (2016). The findings of this study showed that probing and redirecting strategies were most frequently employed by the lecturer, then prompting is quite often used by the lecturer, and repeating was the strategy employed the least. The conclusion of the questioning strategy is the lecturer commitment in teaching English during the classroom interaction to find out whether students understand the material or not and also arouse interest and curiosity about a topic, develop an active learning approach, the end stimulate students to ask themselves and others, to check on students understanding, to obtain information and control the class.